The effect of concentrate supplement feed during prepartum and pre-weaning on the performances of piglets kept by small holders - Pasaribu, Tiurma; Silalahi, M.; Aritonang, D.; Manihuruk, K. (Indonesian Journal of Animal and Veterinary Sciences, 1995)
An experiment has been conducted to study the effect of concentrate feeding supplement on the performances of piglets . Fourty two sows kept individually were used in the experiment. Treatments were assigned to 3x2 factorial completely randomized design consisting of breed (local, crossed and exotic) and feeding (with and without concentrate diets). The experiment results shown that number of piglets at birth and weaning and liveability of piglets had no different between all treatments (breed and feeding supplement) . The average weight gain of piglets at birth litter and at weaning, growth rate, feed consumption along suckling per head or per kg weaning pig have different results between breed and feeding approved . Key words: concentrate, prapartum, lactation and piglets performance